PREVALENCE OF HYDATID CYSTS IN LIVER AND LUNGS OF CATTLE SLAUGHTERED IN SELECTED ABATTOIRS IN NORTHERN NIGERIA - Luka, Sodangi; Kogi, E.; Ndams, I. S.; Kogi, A. C.; Yaro, C. A.; Yakubu, R.; Kase, S. N.; Bello, R.; Yusuf, B.; Haruna, J. S.; Mohammed, A. T.; Mohammed, S. J.; et al. (FUDMA JOURNAL OF SCIENCES, 2023)
This study was conducted to determine the prevalence and fertility of Hydatid cysts of Echinococcus granulosus in Cattle slaughtered in selected abattoirs in Northern Nigeria and Federal Capital Territory (FCT) from February to December, 2022. Gross examination was carried out by visual inspection and palpation of lungs and liver of 1,881 Cattle in order to determine the availability and organ localization of hydatid cysts. A total of 95(5.1%) of the study population harboured one or more cysts in liver and lungs. Highest prevalence was recorded in cattle slaughtered in Gombe State (10.9%) followed by Kaduna (6.2%) the least was in Kogi State (1.9%). The difference of prevalence among the states was statistically significant (p0.05); ...
Keywords: Prevalence; Hydatid cysts; Cattle; Abattoir; Northern Nigeria